Plakophilin 2A is the dominant isoform in human heart tissue: consequences for the genetic screening of arrhythmogenic right ventricular cardiomyopathy. Issue 10 (3rd March 2011) - Gandjbakhch, E; Charron, P; Fressart, V; Lorin de la Grandmaison, G; Simon, F; Gary, F; Vite, A; Hainque, B; Hidden-Lucet, F; Komajda, M; Villard, E
Abstract : Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited heart disease in which mutations affecting Plakophilin-2 ( PKP2 ) are the most frequently detected. However, pathogenicity of variants is not always fully determined. PKP2 encodes two isoforms, the longest (PKP2b) includes the alternatively spliced exon 6, which is routinely screened for molecular diagnosis, despite the absence of data on cardiac expression of PKP2 isoforms. Objective: To examine the pathogenicity of PKP2 exon 6 mutations by focusing on a missense variant located in this exon. Methods and results: The PKP2 heterozygous p.Arg490Trp variant was identified in two unrelated ARVC probands (absent from 470 controls). In silico analysis suggested that PKP2 exon 6 is an Alu-derived sequence with very low expression level. PKP2a mRNA, which does not include the sequence encoded by exon 6, was the dominant isoform transcribed; at western blot analysis PKP2A was the only clearly detectable isoform in all human heart samples analysed (from six different controls and the proband). Moreover, in the proband's sample, p.Arg490Trp was not associated with aberrant exon 6 splicing or mutant mRNA downregulation. Finally, a heterozygous missense variant (p.Glu2343Lys) in Desmoplakin was identified in this proband and is likely to be the disease-causing mutation. Conclusion: PKP2A was shown to be the major isoform expressed in human heart tissue and PKP2B protein was undetectable. The results strongly suggest that p.Arg490Trp and other variants located in PKP2 exon 6 may not be disease causing. Variant splicing also has important consequences for the interpretation of mutation analysis and genetic counselling in ARVC and other hereditary cardiac diseases.